Thermal and flow performance analysis of a concentrated linear Fresnel solar collector with transverse ribs - Hasan, Husam Abdulrasool; Sherza, Jenan S.; Abed, Azher M.; Togun, Hussein; Ben Khedher, Nidhal; Sopian, Kamaruzzaman; Mahdi, Jasim M.; Talebizadehsardari, Pouyan (Frontiers in Chemistry, 2023)
This paper deals with the impact of including transverse-ribs within the absorber tube of the Concentrated Linear-Fresnel collector (CLFR) with a secondary Compound Parabolic Collector (CPC) on thermal and flow performance coefficients. The enhancement rates of heat transfer owing to varying governing parameters were compared and analysed parametrically at Reynolds numbers of (Re = 5000 – 13000) with employing water as the heat transfer fluid. The simulation runs were performed to solve the governing equations using the finite volume technique (FVM) under various boundary conditions. For all Reynolds numbers, the average Nusselt number in the circular tube in the CLFRC system with ribs was found to be larger than that of the plain absorber tube. Also, the inclusion of transverse-ribs inside the absorber tube increases the average Nusselt number by around 115% at Re = 5000 and 175% at Re = 13000. For all Reynolds numbers, the skin friction coefficient of the circular tube with ribs in the CLFRC system is larger than that of the plain absorber tube. The coefficient of surface friction reduces as the Reynolds number increases. The performance assessment criterion was found to vary between 1.8 and 1.9 as the Reynolds number increases.